(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Comprehensive analysis of the literature and language space of the regions of Russia allows us to identify common and distinctive features of different regions and to create a basis for the further development of literary and linguistic regionalistics studies. This makes the paper of urgency. The purpose of the article is to describe current trends in the regional literary and language space study. It includes the following: study of regional literature, language analysis of local authors’ works, regional onomastic space analysis, and urban epigraphy systematic description. The main approach of the issue study is to examine the regional literature and language space as an integral self-developing system existing in a certain environment, on the one hand, and as a means and a necessary condition for the formation and development of a regional personality, on the other. The analysis of the material presented in the article allowed the authors to draw the conclusion that these areas of research are relevant at the present stage of the development of literary and linguistic regionalistics and contribute to its further development. The materials of the article can be useful for carrying out comparative studies in different regions, in lexicographical practice, as well as in teaching philological courses in school and high school.